1995
DOI: 10.1007/bf00231716
|View full text |Cite
|
Sign up to set email alerts
|

Independent contributions of the orienting of attention, fixation offset and bilateral stimulation on human saccadic latencies

Abstract: In a series of experiments we examined the effects of the endogenous orienting of visual attention on human saccade latency. Three separate manipulations were performed: the orienting of visual attention, the prior offset of fixation (gap paradigm) and the bilateral presentation of saccade targets. Each of these manipulations was shown to make an independent contribution to saccade latency. In experiments 1 and 2 subjects were instructed to orient their attention covertly to a location by a verbal pre-cue; tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
107
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 46 publications
8
107
1
Order By: Relevance
“…Similar effects of voluntary orienting of attention on saccadic eye movements have also been observed (13). Moreover, inhibition has been found for saccadic eye reaction time when the visual target is presented at the same position as the cue (8,14,15) or in another peripheral position in the same hemifield (12,14,15).…”
supporting
confidence: 70%
“…Similar effects of voluntary orienting of attention on saccadic eye movements have also been observed (13). Moreover, inhibition has been found for saccadic eye reaction time when the visual target is presented at the same position as the cue (8,14,15) or in another peripheral position in the same hemifield (12,14,15).…”
supporting
confidence: 70%
“…Moreover, our patients even showed shorter saccade latencies compared to the foveal distracter condition when the distracter appeared ipsilesionally and the target was in the contralesional hemifield, a situation that should have induced a disengagement deficit. Finally, it has been shown that whether attention is engaged at fixation or not does not change the extent of facilitation observed in the gap condition (Kingstone and Klein, 1993;Walker et al, 1995). These considerations suggest that attentional disengagement primarily affects processing of stimuli presented in the visual periphery, but is unlikely to explain the bilateral effect of a foveal distracter on saccadic latencies and the absence of an effect on manual RTs.…”
Section: Discussionmentioning
confidence: 96%
“…First, in comparison to an overlap condition the offset of a central fixation stimulus shortly prior to appearance of the target significantly reduces saccade latency (Saslow, 1967), a phenomenon known as the gap effect. Second, a distracter presented simultaneously with the target, but in the opposite hemifield, systematically increases saccade latency, which has been termed the remote distracter effect (Walker et al, 1995(Walker et al, , 1997. Both effects are specific to eye movements and have been attributed to inhibitory interactions within the oculomotor system, in particular the superior colliculus Wurtz, 1992, 1993b;Walker et al, 1997;Gandhi and Keller, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several investigators have suggested that covert shifts of attention may operate and have evolved as preparatory mechanisms for the control of overt shifts in eye fixations (cf. Rizzolatti et al, 1987;Umiltà et al, 1991;Walker, Kentridge, and Findlay, 1995). Shifts of attention precede shifts of the eyes to the same location (cf.…”
Section: Introductionmentioning
confidence: 99%